# Graph 6y=-6-6x 6y=-6-6x
Divide each term by 6 and simplify.
Divide each term in 6y=-6-6x by 6.
6y6=-66+-6×6
Cancel the common factor of 6.
Cancel the common factor.
6y6=-66+-6×6
Divide y by 1.
y=-66+-6×6
y=-66+-6×6
Simplify each term.
Divide -6 by 6.
y=-1+-6×6
Cancel the common factor of -6 and 6.
Factor 6 out of -6x.
y=-1+6(-x)6
Cancel the common factors.
Factor 6 out of 6.
y=-1+6(-x)6(1)
Cancel the common factor.
y=-1+6(-x)6⋅1
Rewrite the expression.
y=-1+-x1
Divide -x by 1.
y=-1-x
y=-1-x
y=-1-x
y=-1-x
y=-1-x
Rewrite in slope-intercept form.
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Reorder -1 and -x.
y=-x-1
y=-x-1
Use the slope-intercept form to find the slope and y-intercept.
Find the values of m and b using the form y=mx+b.
m=-1
b=-1
The slope of the line is the value of m, and the y-intercept is the value of b.
Slope: -1
y-intercept: -1
Slope: -1
y-intercept: -1
Any line can be graphed using two points. Select two x values, and plug them into the equation to find the corresponding y values.
Choose 0 to substitute in for x to find the ordered pair.
Replace the variable x with 0 in the expression.
f(0)=-(0)-1
Simplify the result.
Multiply -1 by 0.
f(0)=0-1
Subtract 1 from 0.
f(0)=-1
The final answer is -1.
-1
-1
The y value at x=0 is -1.
y=-1
y=-1
Choose 1 to substitute in for x to find the ordered pair.
Replace the variable x with 1 in the expression.
f(1)=-(1)-1
Simplify the result.
Multiply -1 by 1.
f(1)=-1-1
Subtract 1 from -1.
f(1)=-2
The final answer is -2.
-2
-2
The y value at x=1 is -2.
y=-2
y=-2
Create a table of the x and y values.
xy0-11-2
xy0-11-2
Graph the line using the slope and the y-intercept, or the points.
Slope: -1
y-intercept: -1
xy0-11-2
Graph 6y=-6-6x   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top